2016
DOI: 10.1038/srep22078
|View full text |Cite
|
Sign up to set email alerts
|

Host kinin B1 receptor plays a protective role against melanoma progression

Abstract: Melanoma is a very aggressive tumor that arises from melanocytes. Late stage and widely spread diseases do not respond to standard therapeutic approaches. The kallikrein-kinin system (KKS) participates in biological processes such as vasodilatation, pain and inflammatory response. However, the role of KKS in tumor formation and progression is not completely understood. The role of the host kinin B1 receptor in melanoma development was evaluated using a syngeneic melanoma model. Primary tumors and metastasis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…At the end of the protocol, lung metastases were screened. Animals treated with DABK presented a lower number of metastatic colonies as compared with animals treated with vehicle ( Figure 2A ), corroborating the previous findings that kinin B1 receptor has a positive role protecting the host from metastatic melanoma colony establishment (Dillenburg-Pilla et al, 2013; Maria et al, 2016). Differences in gain or loss of weight observed during the period studied were not statistically significant ( Figure 2B ).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…At the end of the protocol, lung metastases were screened. Animals treated with DABK presented a lower number of metastatic colonies as compared with animals treated with vehicle ( Figure 2A ), corroborating the previous findings that kinin B1 receptor has a positive role protecting the host from metastatic melanoma colony establishment (Dillenburg-Pilla et al, 2013; Maria et al, 2016). Differences in gain or loss of weight observed during the period studied were not statistically significant ( Figure 2B ).…”
Section: Resultssupporting
confidence: 90%
“…Corroborating these data, immunohistochemistry analysis showed increased expression of VEGF in lungs of B1 −/− DABK-treated mice ( Figure 6C ). Moreover, in our previous study (Maria et al, 2016), we did not observe differences in the number of melanoma colonies established in the lungs of non-treated B1 −/− mice compared to non-treated WT animals and found an increased number of vessels in the lungs of B1 −/− mice.…”
Section: Resultsmentioning
confidence: 40%
See 2 more Smart Citations
“…The overall effect of BK through either B1R, B2R, or both is to promote vascular cell proliferation [ 103 ], influence barrier permeability [ 104 ] and possibly stimulate the release of pro-inflammatory cytokines [ 105 ]. The role of kinin receptors has been investigated in various types of cancer, including melanoma, renal, prostate, lung and breast and mesothelioma [ 106 110 ], among others. Recently our laboratory found that both human and mouse CRC cell lines showed a strong positive expression of B1R and B2R, and while the inhibition of both receptors delayed tumor growth, only B1R blockade reduced tumor load and increased tumor apoptosis [ 105 ].…”
Section: Introductionmentioning
confidence: 99%